2005
DOI: 10.2298/fuee0503467k
|View full text |Cite
|
Sign up to set email alerts
|

Recursive least squares method in parameters identification of DC motors models

Abstract: The procedure of parameters identification of DC motor model using a method of recursive least squares is described in this paper. To identify the system an experimental measuring of signals was carrying out at input-supply of voltage and output of the system for identification-motor angle speed. For the needs of the experiment, a system has been configured with a motor and an optical encoder whose output is connected with the counter input of acquisition card LCK-6013 which over a block connector CB-68LP make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 1 publication
0
17
0
1
Order By: Relevance
“…The validity of the proposed method was shown by simulation an experiments. By comparing a graphic of real motor speed and a graphics of speed of investigated models in a Z and S domains it can be concluded that a satisfying quality of DC motor parameters identification has been achieved [13].…”
Section: Literature Reviewmentioning
confidence: 94%
“…The validity of the proposed method was shown by simulation an experiments. By comparing a graphic of real motor speed and a graphics of speed of investigated models in a Z and S domains it can be concluded that a satisfying quality of DC motor parameters identification has been achieved [13].…”
Section: Literature Reviewmentioning
confidence: 94%
“…In order to show the performance comparison of the constrained estimators discussed above, we consider an example of a DC motor (adopted in [9] and [10]) whose dynamic behavior can be described using the two following equations:…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…According to the researches overviewed, motor parameters have been identified by different methods. For example, the authors in [3,4] used the RLS method to identify the DC motor parameters. G. Mamani et al proposed an online algebraic DC motor parameter estimation in [5].…”
Section: Introductionmentioning
confidence: 99%